Idiopathic Mondor's Disease of the Breast in an Outpatient Primary Care Center: A Case Report - Castro-Goyes, Daniel Fernando; Cepeda-Trillos, Andrea Carolina (Iatreia)
Introduction: Mondor's Disease (MD) is a thrombophlebitis of the anterolateral chest wall, with only about 400 cases reported worldwide, predominantly in women. We report a case of MD with sudden onset of pain, edema, and asymmetry in the left breast, evolving over two weeks. Objectives: To present a case of breast MD identified in an outpatient primary care center in Bogotá, Colombia, as a contribution to broaden the understanding of this disease, raise awareness among healthcare teams about the importance of early identification and appropriate treatment, and contribute to the characterization of MD in the country. Findings: Physical examination revealed edema in the outer quadrants of the left breast associated with a visible longitudinal lesion in the upper outer quadrant (UOQ), tender to palpation. Ultrasound evidence confirmed superficial venous thrombosis. Interventions: A breast ultrasound was performed, showing vascular dilation in the UOQ of the left breast. A breast specialist evaluation was conducted to confirm the diagnosis of MD. Medical management included anti-inflammatory drugs and local heat application, resulting in favorable evolution. Conclusions: MD is an unusual condition in primary care settings, requiring greater awareness among healthcare teams for improved early identification.